Gabrielė Petkevičaitė-Bitė: neįgalaus kūno asmens savivokos formavimosi įtampa - Birgerytė, Aistė (Literatūra, 2015)
The paper presents an interpretation of the autobiographic writings of Gabrielė Petkevičaitė-Bitė, a prominent Lithuanian female writer and a cultural character of the late 1890s and early 1900s. The paper analyses why the disabled female writer had never put any stress on her illness in public (in her childhood she had a twisted spine and stayed a “hunchback” for the rest of her life, had a week nervous system, later had a softened knee-joint and barely could walk, and at the end of her life, she hardly could see and hear). Rather opposite, she identified herself with straight positive views – aspiring “to work for the welfare of the public”, “to disregard private interests” – and even ignored her private experience altogether. On the foundation of the contemporary cultural theories of disability (Simi Linton, Rosemarie Garland Thomson, Lennard J. Davis), the paper aims to reveal the formation of Bitė’s dual rhetorics which uncovers the history of the writer’s identity and the dramatism of her eternal existence “between”. From the point of view of the disability studies, the paper looks into the life of the writer’s parents’ family, which largely shaped Bitė’s consciousness and predetermined her choices. The paper investigates the link between the Bitė’s family philanthropic ideology and personal circumstances (in addition to Gabrielė, there were four other sick children, in Petkevičiai family); the writer’s parents’ attitude towards their daughter’s disability (lameness was not interpreted negatively, it was generally ignored); the father’s arguments not to allow the disabled daughter to pursue higher education. The paper also discusses the issue of the positive outlook on different nations, languages, cultures and gender and reserved opinions about disability that existed in Petkevičiai family. The paper concludes that the background of the writer’s parents’ family, discussed from the point of view of the cultural disability studies, essentially shaped Bitė’s consciousness, her self-identity, personal choices and the public expression of her views.